Maḍāmīn al-Khiṭāb al-Tārīkhī wa-Tajallīyātuhu fī al-Shiʻr al-ʻUmānī al-Ḥadīth: Dirāsah Dalālīyah - Darwāshah, Ḥusayn ʻUmar; Jālūdī, ʻUlayyān ʻAbd al-Fattāḥ (al-Muʼtamar al-Duwalī al-Rābiʻ bi-Mālīziyā: al-Risālah al-Ḥaḍārīyah lil-Adab al-ʻUmānī, 2017)
Omanis have woven historical discourse with skill into the structures of their poetic texts, so that their verse carries varied historical content on subjects and questions marked by depth of feeling for the events and circumstances through which Arab and Islamic societies have passed. Given the close kinship between history and literature, this research studies the content and manifestations of historical discourse in modern Omani poetry and uncovers its significations through four lines of inquiry: the content of historical discourse in modern Omani poetry and its meanings, treated through analytical approaches; the manifestations of historical discourse read in context; the aesthetics of the structures of historical-discourse texts and their systemic devices in modern Omani poetry; and the strategic vision Omani poets bring to historical events and crises in their modern verse. All of this is set out by the descriptive and analytical method, with examples drawn from Omani poetry collections and specialist Omani studies, in order to establish the aesthetics of poetic expression and the meanings latent in this discourse, and to add a serious new study to the library of Omani literature.
MHF-ADAB2017-006
Keywords: Omani poetry; Historical discourse; Semantics; Modern Arabic literature; Literary analysis